A systematic review of UK-based long-term nonsurgical interventions for people with severe obesity (BMI ≥35 kg m-2 ) - Aceves-Martins, M; Robertson, C; Cooper, D; Avenell, A; Stewart, F; Aveyard, P; de Bruin, M; REBALANCE team (Wiley, 2020)
Introduction The aim of this project was to systematically review UK evidence on the effectiveness of long‐term (≥12 months) weight management services (WMSs) for weight loss and weight maintenance for adults (≥16 years) with severe obesity (body mass index ≥35 kg m−2), who would generally be eligible for Tier 3 services.